PRODUCT DIVERSIFICATION TO INCREASE THE COMPETITIVENESS OF THE SMES SCALE COCOA INDUSTRY IN SOUTH SULAWESI WITH QFD AND KANSAI ENGINEER - Lamatinulu Lamatinulu; Noer Rezky Pratama Patta; A Dwi Wahyuni P (Journal of Industrial Engineering Management, 2021)
Packaging is a product attribute that is very important to maintain product quality and has a role as an attraction for consumers. Packaging also serves to protect the product and as a marketing medium. The purpose of this study was to identify the aspects needed in designing the packaging attributes of processed cocoa products. The method used in this research is the Kansei Engineering approach. The instrument used in data collection is a questionnaire to identify Kansei words which are used to develop the basic concept of product packaging design as a result of diversification. From the result of this research is the formulation of the concept of packaging design for industrial chocolate products on an SME scale based on Kansei Word. The initial results of collecting Kansei words were found to be 242 words. The results of the analysis of the similarity of meanings and the grouping of Kansei words, it was found that 15 Kansei words could be used in formulating the concept of packaging design for diversified chocolate products